2011
DOI: 10.1002/ajmg.b.31247
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic psychiatric characterization of children with Williams syndrome and response of those with ADHD to methylphenidate treatment

Abstract: Williams syndrome (WS) is associated with cognitive deficits, special behavioral phenotype, and high rates of psychiatric disorders. The aims of the present study were: (1) To compare the rates of psychiatric disorders and repetitive behaviors in children with WS to children with idiopathic developmental disability (DDs); (2) To longitudinally assess the change in psychiatric disorders during adolescence in WS; (3) To assess retrospectively the effectiveness and safety of methylphenidate (MPH) treatment in WS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 48 publications
1
23
0
2
Order By: Relevance
“…High emotionality is defined as the tendency to become upset easily and intensely. The high emotionality in 22q11.2DS and WS is probably also reflected in the high rates of ADHD and ODD in the two syndromes [5-7]. We believe that the high emotionality of individuals with the two syndromes stems from a biological impairment of mood regulation and disinhibition, and the tendency of these individuals to respond with great intensity when confronted with difficulties [4,38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High emotionality is defined as the tendency to become upset easily and intensely. The high emotionality in 22q11.2DS and WS is probably also reflected in the high rates of ADHD and ODD in the two syndromes [5-7]. We believe that the high emotionality of individuals with the two syndromes stems from a biological impairment of mood regulation and disinhibition, and the tendency of these individuals to respond with great intensity when confronted with difficulties [4,38].…”
Section: Discussionmentioning
confidence: 99%
“…The two syndromes are associated with high rates of psychiatric disorders including attention deficit/hyperactivity disorder (ADHD), oppositional defiant disorder (ODD), and phobias. Social anxiety disorder is more prevalent in 22q11.2DS while specific phobia is more common in WS [5-7]. Up to one-third of individuals with 22q11.2DS develop schizophrenia-like psychotic disorders during adolescence and early adulthood, making 22q11.2DS the most commonly known genetic syndrome associated with schizophrenia [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on individuals with WS showed that the combination of SSRIs and low doses of low-potency antipsychotics seems to be the most suitable medication to treat Generalized Anxiety disorder [68]. In a study on response to methylphenidate treatment of individuals with WS and with ADHD, a decrease in the rate of Anxiety disorders and clinically significant improvement were reported [69]. However, the evidence base for specific psychopharmacologic treatment in populations with ID is limited and warrants future prospective controlled trials for a more targeting intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Os pacientes apresentam um comportamento hipersociável, inclusive com estranhos (Gosch e Pankau, 1994;Doyle et al, 2004), porém com relacionamentos interpessoais muitas vezes inapropriados (Einfeld et al, 1997). Sintomas como ansiedade excessiva, fobias, sintomas obsessivos-compulsivos, comportamentos estereotipados, distúrbios do sono, déficit de atenção e hiperatividade podem ser encontrados desde a infância na SWB, podendo exigir terapia farmacológica (Udwin e Yule, 1991;Bawden et al, 1997;Einfeld et al, 1997;Power et al, 1997;Green et al, 2012). Com a idade, sintomas depressivos podem surgir em alguns pacientes (Einfeld et al, 1997), contrastando com a personalidade expansiva observada previamente na infância.…”
Section: Características Clínicasunclassified